Scoping Review: Study of Herbs Consumption for Self-Medication in Indonesia 2019-2022 - Azzahra, Fatimah; Astuti, Ayun Dwi; Arifin, Bustanul; Alam, Gemini (Majalah Obat Tradisional, 2024)
Indonesia is a country that has high biodiversity and is rich in traditional medicine from natural ingredients or herbs. One use of these natural ingredients is as a treatment for self-medication. Many previous studies have been carried out but none has reviewed it systematically, especially during the Covid-19 pandemic. This research was carried out systematically using the PRISMA statement approach using the Google Scholar data bank. Out of 2,214 papers in the 2019-2022 period,  45 articles/scientific papers papers met the criteria, including inclusion and exclusion criteria, for a description/profile of the use of natural ingredients or herbs as self-medication for traditional medicine. The central region of Java (D.I.Y Yogyakarta and Central Java) is the region with the largest number of articles. The distinctiveness of Indonesia's approach to self-medication lies in its utilization of various natural elements to address similar ailments, which can be attributed to geographical factors, cultural beliefs, and diverse knowledge across different regions. Meanwhile, Covid-related studies were very limited due to the availability or the preference for chemical self-medication.